Misperceiving grandiose narcissism as self-esteem: why narcissists are well liked at zero acquaintance - Giacomin, Miranda; Jordan, Christian H. (My University, 2018)
Objective: We examine why people form positive first impressions of grandiose narcissists, even though they can identify others’ narcissism. We test whether this occurs because narcissists are perceived to have especially high self‐esteem, which is socially valued. Method: Across four studies, undergraduate perceivers viewed photographs of targets (for whom narcissism and self‐esteem were known) and rated perceptions of their narcissism and self‐esteem, as well as how much they liked them. Results: Perceivers rated more narcissistic targets to be higher in self‐esteem (even compared to targets with equally high self‐esteem) and liked them more. Perceptions of self‐esteem, moreover, mediated the effect of target narcissism on liking (Study 1). This effect disappeared when targets’ narcissism was made salient, suggesting that trait narcissism is not inherently attractive (Study 2). Finally, path models revealed a negative effect of perceptions of narcissism on liking that was suppressed by a positive effect of perceptions of self‐esteem on liking (Study 3a), even for ratings of people’s online dating profiles (Study 3b). Conclusions: Positive initial impressions of narcissists may be driven by inflated perceptions that they have high self‐esteem.
Keywords: impression formation; narcissism; person perception; self‐esteem